Histopathological effects of some helminthic parasites on the liver of Serranid fish - Maghrabi, Omaimah (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
In this study, histopathological effect of different helminthes on the liver of different Serranid fish has been investigated. The fishes examined for liver helminth infections are Epinephelus tauvina , Epinephelus polyphekadion , Epinephelus summana , and Epinephelus chlorostigma. Herein , helminthes were identified as Anisakis simplex larvae; Thynnascaris larvae; Procamallanus chetumalensisn. sp. , and Camallanus hypophthalmicthys. The parasites were found in blood sinusoids in between the blood cells and among the hepatocytes.Microscopical examination of liver tissue revealed different histopathological and cellular lesions in liver of infected fishes .The pathological alterations included, extensive vacuolization and destruction of most hepatocytes and blood vessels, accumulation of lipid droplets,congestion of blood sinusoids and focal hemmorage .The heavily infected fish species was E. polyphekadion and the intense infestation was recorded for the parasites Anisakis simplex larvae (Rudolphi, 1809) and Thynnascaris larvae (Dollfus, 1933